An Analytical and Experimental Evaluation of a Heat Sink Under Constant Heat Flow and Forced Convection Heat Transfer - Ehsan Fadhil Abbas (Journal of Engineering and Technological Sciences, 2021)
In this study, the exact transient differential equation was used to calculate the convection heat loss in a heat sink with a rectangular cross section fin. The result of the analytic solution was compared to the result from experiments conducted on a standard heat sink. The experiments were performed at a constant heat flow of 9000 W/m2 and a low airflow rate ranging from 12 to 100 cm3/s in seven steps. The comparative results showed that while there was good agreement between the experimental result and the exact solution, the average error ratio increased with an increase of the airflow rate. However, the maximum average error ratio between the experimental result and the exact solution did not exceed 6.4%. The maximum temperature distribution in the heat sink was obtained at a time of 900 s in all experiments.